2013
DOI: 10.1080/00423114.2013.859281
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a Kalman filter-based model for vehicle slip angle estimation

Abstract: It is well known that vehicle slip angle is one of the most difficult parameters to measure on a vehicle during testing or racing activities. Moreover, the appropriate sensor is very expensive and it is often difficult to fit to a car, especially on race cars. We propose here a strategy to eliminate the need for this sensor by using a mathematical tool which gives a good estimation of the vehicle slip angle. A single-track car model, coupled with an extended Kalman filter, was used in order to achieve the resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
53
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(60 citation statements)
references
References 11 publications
1
53
0
Order By: Relevance
“…That is, due to simplified tyre models that operate only in the linear zone (adapting the cornering stiffness to expand its usage range) but neglecting the non-linear and saturation zone behaviour. In a similar work [24], the tyre model adaption regards the entire non-linear range. By using a standard family of curves representing a generic Pacejka model dataset and an integrated tuning procedure for the EKF observer, the authors managed to develop a tyre model that was consistent with the lateral behaviour.…”
Section: Kalman Filtermentioning
confidence: 99%
See 1 more Smart Citation
“…That is, due to simplified tyre models that operate only in the linear zone (adapting the cornering stiffness to expand its usage range) but neglecting the non-linear and saturation zone behaviour. In a similar work [24], the tyre model adaption regards the entire non-linear range. By using a standard family of curves representing a generic Pacejka model dataset and an integrated tuning procedure for the EKF observer, the authors managed to develop a tyre model that was consistent with the lateral behaviour.…”
Section: Kalman Filtermentioning
confidence: 99%
“…• the use of single track vehicle models (also known as the bicycle model), e.g., [16,24,120] by Cheli et al, Gadola et al and Naets et al; • the assumption of the availability of the vehicle longitudinal speed, so that the first equation in Equation (7) is not used, e.g., [16,24,26] A set of equations similar to Equation (7) needs to be coupled with a tyre model, so as to express the forces as functions of the relevant slip parameters, e.g., longitudinal slip ratio and slip angle, respectively for longitudinal and lateral forces. In the literature, there are several approaches, e.g., the use of linear models, Pacejka models (also known as Magic Formula models), alternative tyre models (e.g., rational tyre model [122], Dugoff model [123], Burckhardt model [124]).…”
Section: Kalman Filtermentioning
confidence: 99%
“…In the latest study, I found that most of the vehicle models estimating vehicle state based on the EKF, cubature Kalman filter (CKF), or unscented Kalman filter (UKF) algorithm use a simple motorcycle model, a simple motorcycle model with the tire magic formula, or a simple 3-DOF vehicle model, which do not take into account the effects of vehicle body roll motion. 29,30 So, a nonlinear 3-DOF vehicle model including the longitudinal, lateral, and yaw direction is proposed for estimating the road curvature in real time considering roll motion of vehicle body (see Figure 5). …”
Section: -25mentioning
confidence: 99%
“…Several side-slip angle estimation strategies have been proposed in literature. They are mainly based on Extended Kalman Filters (EKF) [3][4][5]. Since EKF typically requires a reference vehicle model, it is able to provide a good estimation only if model parameters are accurately known.…”
Section: Introductionmentioning
confidence: 99%